(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses various methods of professional orientation in teaching specific subjects, professional orientation printing in higher education, the functions of professional orientation printing, methodological aspects of professional orientation (the use of various methods,methods and forms and software of education), as well as the principles that help to implement professional orientation: science, the direction of the organization, fundamentalism.